2011
DOI: 10.1007/s11596-011-0566-1
|View full text |Cite
|
Sign up to set email alerts
|

The cross-talk between ROS and p38MAPKα in the Ex Vivo expanded human umbilical cord blood CD133+ cells

Abstract: This study investigated the correlation between and compared the effects of reactive oxygen species (ROS) and p38 mitogen-activated protein kinase α (p38MAPKα) in the ex vivo expanded umbilical cord blood (hUCB) CD133(+) cells. hUCB CD133(+) cells were cultured in the hematopoietic stem cells (HSCs) culture medium with N-acetylcysteine (NAC, an anti-oxidant), p38MAPKα-specific inhibitor (SB203580) or their combination. The levels of ROS and expression of phosphorylated p38MAPKα (p-p38) in CD133(+) cells were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 24 publications
2
1
0
Order By: Relevance
“…Consistently, our previous study demonstrated that wogonin, another important component of S. baicalensis Georgi, activates ROS to promote TRAIL-induced apoptosis (13). It is also known that the activation of p38 is often mediated by ROS (19)(20)(21)(22). However, the results of the present study revealed that baicalin and TRAIL-induced activation of p38 is independent of ROS.…”
Section: Discussionsupporting
confidence: 90%
“…Consistently, our previous study demonstrated that wogonin, another important component of S. baicalensis Georgi, activates ROS to promote TRAIL-induced apoptosis (13). It is also known that the activation of p38 is often mediated by ROS (19)(20)(21)(22). However, the results of the present study revealed that baicalin and TRAIL-induced activation of p38 is independent of ROS.…”
Section: Discussionsupporting
confidence: 90%
“…The activation is likely attributable to oxidative stress resulting from culture of hUCB HSCs in vitro in a normoxic condition (20% of O 2 ) [15, 16]. This suggestion is supported by the findings from a separate study which was published recently by our group [38]. In that study, we found that hUCB CD133 + cells exhibited a significant increase in ROS production and p38 activation after ex vivo expansion.…”
Section: Discussionsupporting
confidence: 74%
“…We suspect that the low oxygen environment of the tumor may have contributed to the development of CD34 + cells with a low redox status that could explain a higher ability to engraft. In addition, a lot of efforts are actually made in order to maintain or restore the stemness of HSPCs by the use of NOXs inhibitors, antioxidants molecules and hypoxic culture, alone or in combination (22,72,(88)(89)(90)(91). Indeed, one limit of the hematopoietic differentiation protocol used in this study is that experiments were conducted under 21% oxygen, and not in hypoxia conditions like HSCs located in a hypoxia niche inside the bone marrow.…”
Section: Discussionmentioning
confidence: 99%